2019
DOI: 10.21873/anticanres.13279
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-specific Monocyte Chemotactic Protein-1 Deficiency Reduces Pulmonary Metastasis of Lewis Lung Carcinoma in Mice

Abstract: Aim: Monocyte chemotactic protein-1 (MCP1) is a potent adipokine. This study tested the hypothesis that adiposeproduced MCP1 contributes to metastasis. Materials and Methods: In a spontaneous metastasis model of Lewis lung carcinoma (LLC), male adipose MCP1-deficient (Mcp1 −/− ) and wild-type (WT) mice were fed the AIN93G diet or a high-fat diet (HFD) for 11 weeks. Lung metastasis from a subcutaneous tumor was the primary endpoint. Results: The adipose expression of MCP1 was lower in Mcp1 −/− mice than in WT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Mediated the infiltration of monocyte and macrophage to the site of inflammation Its expression correlates with body BMI and adiposity [40] Fetuin-A Promotes IR by inhibition of insulin receptor's tyrosine kinase activity Mainly secreted by the liver and taken up by AT AT secreted fetuin-A increases in metabolic syndrome [34] [41] [42] generated in WAT from a non-myf-5 lineage [48]. Both types of brown adipocyte express uncoupling protein 1 (UCP1) on the inner mitochondrial membrane.…”
Section: Adipose Tissue Structure and Biologymentioning
confidence: 99%
“…Mediated the infiltration of monocyte and macrophage to the site of inflammation Its expression correlates with body BMI and adiposity [40] Fetuin-A Promotes IR by inhibition of insulin receptor's tyrosine kinase activity Mainly secreted by the liver and taken up by AT AT secreted fetuin-A increases in metabolic syndrome [34] [41] [42] generated in WAT from a non-myf-5 lineage [48]. Both types of brown adipocyte express uncoupling protein 1 (UCP1) on the inner mitochondrial membrane.…”
Section: Adipose Tissue Structure and Biologymentioning
confidence: 99%
“…We have reported that adipose specific Mcp-1 knockout reduces high-fat diet-enhanced mammary tumorigenesis in female mice ( 24 ) and metastasis of Lewis lung carcinoma ( 25 ) in male mice. However, the role of adipose-derived MCP-1 in male breast cancer remains unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The close link between MCP-1 and inflammation was revealed by adipose-specific Mcp-1 knockdown mice displaying lowered plasma concentrations of several proinflammatory adipokines viz. leptin, plasminogen activator inhibitor-1 and resistin compared to wild-type controls (16). We believe that the two chemotactic signals, FetA and MCP-1, copiously generated in lipid-enriched AT milieu, can significantly influence ATM content and activation.…”
Section: Introductionmentioning
confidence: 85%